Resposta de porta-enxertos de caramboleira à adubação com zinco - de Lima Neto, Antonio João; Natale, William; Modesto, Viviane Cristina [UNESP] (FapUNIFESP (SciELO), 2015)
Even though the star fruit is widely grown throughout the state of Sao Paulo, it is lacking information on nutrition and fertilization effects on rootstocks star fruit in literature. The study aimed to evaluate plant growth and how much Zn accumulates in star fruit rootstocks subjected to different doses of zinc. The study was conducted between the months of September 2012 and February 2013, on a commercial seedling production nursery, located in Taquaritinga, SP. A randomized block experimental design was used consisting of five doses of zinc: zero, 2.0; 4.0; 6.0 and 8.0 mg dm-3 of Zn. There were four repetitions and three plants per plot. The age of the rootstocks used in the experiment were one year and two months old and were grown in polyethylene bags, with pine bark as substrate. At 170 days after administering the zinc, the plant height, stem diameter, number of leaves, the dry weight of the shoot, roots and total dry weight were recorded. The zinc content in the roots and shoots was determined, following a calculation of the accumulation of Zn in different parts of the plant. Zinc influenced the plant height, stem diameter, leaf emergence and accumulation of dry matter of shoots, roots and total. Found that the greatest development of star fruit rootstocks was associated with the dose between 3.1 and 3.8 mg dm-3 of Zn. High doses of zinc impair the growth and accumulation of the micronutrient in star fruit rootstocks.
Rootstocks to fertilization with zinc
Keywords: Averrhoa carambola L; Micronutrient; Mineral nutrition